Presentación Editorial - Pérez Martínez, Arizbeth Amitzin; Guadarrama Muñoz, Alma Cossette; Vázquez Espinoza de los Monteros, Roberto Antonio (Revista del Centro de Investigación de la Universidad la Salle, 2023)
-